1990
DOI: 10.1128/jb.172.11.6189-6193.1990
|View full text |Cite
|
Sign up to set email alerts
|

The level of a transcript required for production of a Streptomyces coelicolor antibiotic is conditionally dependent on a tRNA gene

Abstract: In Streptomyces coelicolor A3(2), bldA mutants are conditionally defective in aerial mycelium formation and fail to synthesize all four antibiotics produced by bldA+ strains. Previous studies showed that bldA specifies the tRNA for the rarely used leucine codon UUA. Here we describe experiments examining the abundance in a bldA mutant of a transcript involved in antibiotic production. With use of a bacteriophage-based integrative vector, a promotorless xylE reporter gene was inserted into a previously undescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…3) or on the rich medium R2YE. The same result was seen on MM plus mannitol with low phosphate (0.04 mM), conditions in which one of the S. coelicolor antibiotic pathways (for undecylprodigiosin synthesis) is expressed in the bldA39 mutant J1700 (30 (Fig. 4, was used to transform J1725 (S. lividans, bldA39).…”
Section: Resultsmentioning
confidence: 72%
“…3) or on the rich medium R2YE. The same result was seen on MM plus mannitol with low phosphate (0.04 mM), conditions in which one of the S. coelicolor antibiotic pathways (for undecylprodigiosin synthesis) is expressed in the bldA39 mutant J1700 (30 (Fig. 4, was used to transform J1725 (S. lividans, bldA39).…”
Section: Resultsmentioning
confidence: 72%
“…The growth phase is called the trophophase, whereas the secondary metabolite production phase is termed the idiophase (reviewed in reference 29). A strict separation of both phases, with production of secondary metabolites virtually only in the idiophase, has been observed in antibiotic-producing bacterial cultures (19,27). By comparing regulatory circuits of several antibiotic biosyntheses, Martin and Demain (29) concluded that the separation between trophophase and idiophase is not so clearcut in filamentous fungi.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is no TTA codon in redD (Narva and Feiteison, 1990). To explain the btdAdependence of the red structurai genes, Guthrie and Chater (1990) proposed that a second pathway-specific regulatory gene for the red genes which does contain a TTA codon is also necessary for their activation. Why should there be differences in the role of bidA between pathways?…”
Section: Different Antibiotic Pathways Are Influenced By Bida Throughmentioning
confidence: 99%
“…for the actinorhodin and undecylprodigiosin pathways, respectively, show evidence of homology throughout, and they are therefore likely to have a simitar mode of action (FernandezMoreno etai, 1991: Narva andFeitelson, 1990). Representative structural act genes controlled by acfll-ORF4 and red genes controiled by redD are transcriptionally virtually silent in a btdA mutant {Guthrie and Chater, 1990;Bruton et ai. 1991).…”
Section: Different Antibiotic Pathways Are Influenced By Bida Throughmentioning
confidence: 99%